2020
DOI: 10.5604/01.3001.0014.8210
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of postural stability using the Zebris Platform in women above the age of 60

Abstract: Introduction. Balance control and body posture stability disorders progressing with age are caused by the involutionary changes in the function of the motor and nervous systems. However, it is indicated that regular physical activity, also in older adulthood, may have a positive effect on maintaining the functions of individual systems at an optimal level. Study aim: The aim of the study was to assess the postural stability of women above the age of 60 who declare active lifestyles. Material and Methods. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…group and comparison were made based on their COP sway parameters. The result suggested that the older group had a lower level of postural stability compared to the younger group(Jaworski & Kołodziej, 2020).Nevertheless, the force platform has been reported to suffer from several limitations such as high cost (around £11,529), weight (around 10 kg for only the platform), considerable testing area (around 2.5 square metre), difficulty to transport, difficult of use, lack of sensitivity to the weight of children (Estévez-Pedraza et al, 2020; Rodríguez-Rubio et al 2020). Matłosz et al (2020) compared three different and commonly used force platforms among 111 young healthy adult subjects.…”
mentioning
confidence: 93%
“…group and comparison were made based on their COP sway parameters. The result suggested that the older group had a lower level of postural stability compared to the younger group(Jaworski & Kołodziej, 2020).Nevertheless, the force platform has been reported to suffer from several limitations such as high cost (around £11,529), weight (around 10 kg for only the platform), considerable testing area (around 2.5 square metre), difficulty to transport, difficult of use, lack of sensitivity to the weight of children (Estévez-Pedraza et al, 2020; Rodríguez-Rubio et al 2020). Matłosz et al (2020) compared three different and commonly used force platforms among 111 young healthy adult subjects.…”
mentioning
confidence: 93%